Pengaruh Persepsi Siswaatas Kompetensi Pedagogik Guru dan Lingkungan Sekolah terhadap Prestasi Belajar Ekonomi - Ismail Dwi Cahyo; Oktaviandani Nurfitria (LPPM Politeknik Pratama, 2024)
This research aims to determine the influence of students' perceptions on teachers' pedagogical competence and the school environment on the achievement of economic learning. The research method employed is a survey using a correlational technique involving 60 students as samples. The sample selection utilized a random sampling technique. Data analysis involved descriptive statistics such as finding the mean, median, standard deviation, and inferential statistics, including multiple regression analysis, followed by simultaneous and partial significance tests. The results of the study indicate: (1) There is a significant combined effect of students' perceptions on teachers' pedagogical competence and the school environment on the achievement of economic learning in State Senior High Schools in Bekasi City. The significant effect is evidenced by the score of Sig. = 0.000 < 0.05 and F0 = 47.152. Both variables, students' perceptions of teachers' pedagogical competence and the school environment, contributed 62.3% to the achievement of economic learning. (2) There is a significant effect of students' perceptions of teachers' pedagogical competence on the achievement of economic learning in State Senior High Schools in Bekasi City. The significant effect is evidenced by the score of Sig. = 0.000 < 0.05 and t0 = 4.555. (3) There is a significant effect of the school environment on the achievement of economic learning in State Senior High Schools in Bekasi City. The significant effect is evidenced by the score of Sig. = 0.000 < 0.05 and t0= 4.528.